Neurological diagnoses in the emergency room: differences between younger and older patients - Marcos C. Lange; Vera L. Braatz; Carolina Tomiyoshi; Felipe M. Nóvak; Artur F. Fernandes; Laura N. Zamproni; Élcio J. Piovesan; Edison M. Nóvak; Helio A.G. Teive; Lineu C. Werneck (Arquivos de Neuro-Psiquiatria)
Neurological diseases are prevalent in the emergency room (ER). The aim of this study was to compare the neurological diagnoses between younger and older patients evaluated in the ER of a tertiary care hospital. METHOD: Patients admitted to the ER who required neurological evaluation in the first 24 hours were separated into two groups based on age, <;50 years old and >50 years old. RESULTS: Cerebrovascular disease (59.6% vs. 21.8%, p<0.01) was most frequent in the >50 years old group. Seizures (8.1% vs. 18.6%, p<0.01) and primary headache (3.7% vs. 11.4%, p<0.01) were most frequent in the <;50 years old group. CONCLUSION: The current study demonstrated that these three neurological diagnoses represented the majority of the neurological evaluations in the ER. National guidelines for ER teams that treat these prevalent disorders must be included in clinical practice and training.